Impending changes for securities markets : what role for the exchanges? - Bloch, Ernest; Schwartz, Robert A. (Greenwich, Conn. : JAI Press, 1979)
Part 1 presents two papers which establish the historical perspective in which current problems and change should be assessed.
Papers presented at a two-day conference held Jan. 1977.
Includes bibliographies and index.
osc 17/07/2018
Loans
Keywords: Stock exchanges